Targeting BRCA2 deficiency with GSK3 inhibitors - Zonderland, G (2017)
BRCA1 and BRCA2 tumour suppressors are essential for homologous recombination-mediated double-strand break repair and replication fork protection. Therefore, BRCA1 and BRCA2 are essential for cell viability. Deactivating mutations in one of these genes lead to genome instability and are associated with breast and ovarian cancer. We thus performed a chemical library screen and identified glycogen synthase kinase 3 (GSK3) inhibitors as a potent tool to kill BRCA2-deficient cells. One of the best-characterised cellular functions of serine/threonine kinase GSK3 is its role in the WNT pathway. Here, it acts as a regulator of β-catenin, with the inactivation of GSK3 leading to the stabilisation of β-catenin. In this study, we show that inhibition of GSK3 reduces the viability of human BRCA2-deficient cells. In addition, GSK3 inhibition leads to replication stress, DNA damage and genome instability in the context of BRCA2 deficiency. GSK3 inhibition sensitivity can be reversed by depleting β-catenin. Furthermore, GSK3 inhibition-induced replication stress and checkpoint activation is reduced when β-catenin is depleted. BRCA1-deficient cells that have lost 53BP1 are able to overcome PARP inhibitor olaparib sensitivity by reactivating homologous recombination. Interestingly, we find that olaparib-resistant Brca1-/- , 53BP1-deficient cells are sensitive to GSK3 inhibition, whilst Brca1+/+ cells remain unaffected. In summary, these results demonstrate that GSK3 inhibitors may be used to target HR deficiency, including cells that have acquired resistance against currently used therapies.